Bad tickets - O'Dell, Kathleen (Knopf, 2007)
Rebelling against her strict Catholic upbringing in 1967, teenager Mary Elizabeth sorts through her feelings about her parents and friends, and about sex, while making some decisions about the type of life she wants for herself